The evolution of gender studies in physical education: insights from a bibliometric analysis - Arifin, Bustanol; Muzakki, Abdurrohman; Pavlović, Ratko; Setiawan, Edi (Edu Sportivo: Indonesian Journal of Physical Education, 2025)
Background: Highlighting gender in physical education is particularly important due to the prevalence of gender inequalities and stereotypes in this context. Research Objectives: The purpose of this study is to to analyse the development, trends, and patterns of research on gender in physical education. Methods: This research uses bibliometric analysis. The search was initiated using the Scopus and Web of Science (WoS) databases. The results of article findings on the Scopus database showed 242 articles, while the WoS database showed 252 articles. Pre-process bibliographic datasets generated with the ScientoPy tools. Findings/Results: This research shows a growing interest in the topic of gender in physical education since 2005, with a peak in 2023. Publications from different disciplines, such as education, social sciences, sport science, and psychology, demonstrate a multidisciplinary approach to addressing gender inequality. The analysis also identified influential authors, including Daniel Mayorga-Vega and Jesús Viciana, who wrote five articles each. Spain was the largest contributing country, with 105 articles. The keyword “physical activity” appeared 15 times, highlighting the focus on the relationship between physical activity and gender. Conclusion: Bibliometric analyses indicate a strong and growing interest in gender research in physical education. Contributions from influential authors and support from key academic journals have fuelled this progress. Emerging patterns and themes highlight the complexity of gender issues in this context, emphasising the need for ongoing research and practical interventions to promote gender equality. This study provides a comprehensive overview of the evolution of gender research in this field, offering valuable insights for educators, policymakers, and researchers to create an inclusive and equitable physical education environment.